A two-step theory and test of the oil curse: the conditional effect of oil on democratization. Issue 3 (3rd April 2018) - Houle, Christian
ABSTRACT: Does oil impede democratization? This article posits that in order to understand the effect of oil on democratization one has to decompose the transition process into two steps: (1) the ending of the authoritarian regime, which initiates the process; and (2) the subsequent establishment of a democracy rather than an autocracy. I argue that oil has different effects on the two phases of the transition process: while oil has contradictory effects on the likelihood that an authoritarian regime fails, it diminishes the likelihood of the establishment of democracy following the failure. Oil's negative effect is conditional on the breakdown of the authoritarian regime, which itself is unaffected by oil. That is, although oil does not initiate the transition process, it does influence its outcome. Using data on 118 autocracies, I find evidence consistent with this hypothesis.